State of Necessity in Post Covid-19 Investor-State Arbitration: CMS and LG&E Revisited (Dhaka University Law Journal, 2023)
Covid-19 has spread its wrath on every aspect of human affairs. Foreign investment is no exception to that. To combat the pandemic, different States have deployed various restrictive measures having a direct bearing on foreign investors. Such actions are likely to result in an influx of investor-State disputes. It can be reasonably assumed that the States will invoke the necessity plea, among other grounds, to negate their responsibilities in such situations. The cases of The CMS Gas Transmission Company v. The Argentine Republic (2005) and LG&E Energy Corporation v. The Argentine Republic (2006) previously sparked debate about the necessity defence’s applicability in investment arbitrations. This article examines the suitability of the defence in investor-State arbitrations in the post- Covid-19 era in light of the CMS and LG&E cases. After careful scrutinization, this article proposes that the unique nature of the crisis borne from the Covid-19 pandemic should be taken into consideration while applying the defence in any pandemic-induced arbitration. It concludes that unless the catalysts associated with the pandemic are taken into account while applying the defence, it will be invariably futile in investor-State arbitrations.Dhaka University Law Journal, Vol. 33(1), 2023 P.1-22